Vulnerabilities and risks associated with the work of Agentes de Combate à Endemias (Research, Society and Development, 2022)
The study aimed to identify vulnerabilities and health risks, that the ACE (combat endemic diseases agents) are exposed in the exercise of their activities. This is a quantitative research, developed in three municipalities of the western region of Santa Catarina, through a semi-structured questionnaire composed of closed questions, with multiple choice answers and possibility of argumentation. A total of 87 ACE answered the questionnaire in the of period of April and May of 2016. The answers were tabulated in the program Microsoft Office Excel (2007) and the arguments grouped into categories. The most frequently mentioned health risks were environmental, occupational, and social risks. The ACE recognize themselves to be vulnerable to the risks arising from climatic conditions, inappropriate use of personal protective equipment, poor working conditions and the use of chemicals products. Emerging demand for implementation of practices to act on vulnerabilities that are exposed.